Assessing thermal stress on cultural heritage in Limassol: a multi-scale remote sensing approach using Sentinel-3 and Landsat 9 land surface temperature data - Dimitriou, Christodoulos; Themistocleous, Kyriacos; Abate, Dante; Hadjimitsis, Diofantos G. (My University, 2025)
Cultural heritage buildings and archaeological sites in urban environments are increasingly at risk from exposure to thermal stress driven by climate change. This study examines the impact of thermal stress on heritage structures in Limassol’s historic district using Land Surface Temperature (LST) images from Sentinel-3 and Landsat-9 satellite remote sensing data. Sentinel-3’s broader coverage at a 1km spatial resolution allows for a city-wide survey of thermal anomalies, enabling the identification of extensive urban hotspots. Landsat 9’s 30m resolution provides detailed thermal distributions that highlight localized thermal gradients around individual heritage sites, archaeological areas and listed neoclassical buildings, which are more sensitive to small-scale environmental changes. By correlating data from both satellites, this research constructs thermal risk maps, revealing the interplay between large-scale urban heat trends and site-specific vulnerabilities. The results demonstrate that areas with high concentrations of cultural heritage assets that consistently show elevated thermal stress levels face increased risks of material degradation, weathering and accelerated decay in historic structures. These findings underscore the importance of microclimate interventions to urban planning and landscaping to mitigate heat buildup. This multi-scale remote sensing approach offers a replicable framework for other Mediterranean cities facing similar climatic pressures. Integrating broader-scale monitoring with Sentinel-3 with site-focused assessments from Landsat 9 provides a robust tool for heritage preservation policies, restoration efforts, and climate-resilient urban development. Ultimately, the study highlights how the use of satellite LST data can serve as a critical resource for safeguarding historical sites against the impacts of climate change and urban heat island effect
Keywords: Remote sensing; Sentinel-3; Landsat-9; mediterranean; urban heat island; climate change; cultural heritage; thermal stress